Impact of Gut Microbiome on Gut Permeability in Liver and Gut Diseases - Punnag Saha; Phillipp Hartmann (Microorganisms)
Hepatobiliary and gastrointestinal conditions, including chronic liver diseases and inflammatory bowel disease, are associated with significant morbidity and mortality globally. While the pathophysiology and symptoms vary from one disease to another, aberrations of the gut microbiome with deleterious microbial products affecting the intestinal barrier are common in patients suffering from these diseases. In this review, we summarize changes in the gut microbiome associated with various disease states and detail their role in gut barrier disruption and in modulating disease progression. Further, we discuss therapeutic interventions and precision medicine approaches targeting the microbiome, which have shown promise in alleviating these chronic illnesses in mouse models and patients.